THE EFFECTIVENESS OF COMIC STRIP TO IMPROVE THE SECOND GRADE STUDENTS’ ABILITY IN WRITING RECOUNT TEXT IN MTs AL MUTTAQIN - Ulfatun Sariroh (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
The objective of the research is: to find how effective is the use of comic strip to improve students’ ability in writing recount text at the eighth grade of MTs. Al Muttaqin. The research used was quasi-experimental research which carrie out two classes, one for experimental class and the other for controlled class. The population of this research was the eighth grade students, there were 8A for experimental class and 8B for controlled class. The result of the research showed that the used of comic strip in teching writing of recount text was effective. It could be seen from the result of calculating that the students’ gained score in experimental class was higher (22,59) than the students’ gained score in controlled class (18,41). Based on the statistic calculting with significance level of 5%, it showed that to was higher than tt, that was 2,000 > 1,990. Therefore, it prove the alternative hypothesis (Ha), which stated that there was significant diffference between the students’ gained score in learning writing recount text by using comic strip and the students’ gained score in learning writing recount text without using comic strip at the eighth grade of MTs Al Muttaqin.